Obstetrical outcome after B-Lynch sutures and ligation of uterine arteries: A case report - S. Vanwinkel; L. Claes; T. Van den Bosch (Elsevier, 2021)
Objective: To illustrate the obstetrical outcome after B-Lynch sutures and ligation of the uterine arteries. Case: A 26-year-old nulliparous woman. A caesarean section performed for obstructed labour was complicated by uterine atony. A B-Lynch uterine compression suture technique was used combined with ligation of the ascending branches of the uterine arteries. Before the subsequent fertility treatment, gel instillation sonography and power Doppler imaging showed a normal uterine cavity and restored myometrial vascularization. Subsequent caesarean section showed external adhesions on the anterior uterine serosa. A healthy baby of normal weight was delivered. There was focal placenta accreta; the underlying myometrium was strikingly thinner and prone to inversion. Discussion: After B-Lynch sutures and ligation of the ascending branches of the uterine arteries, the pregnancy was subsequently uncomplicated. The potential association between B-Lynch sutures and placenta accreta or uterine inversion in a subsequent pregnancy has to be assessed in further studies. This case report illustrates how 3D gel instillation sonography is a valuable tool to evaluate the integrity of the uterine cavity.